EFFECTS OF FORENSIC ACCOUNTING ON FRAUD DETECTION AND PREVENTION IN BUSINESS ORGANISATIONS IN NIGERIA (Journal of Contemporary Issues in Accounting, 2022)
There has been an upward surge in financial fraud worldwide over the past decade. Uncovering these frauds is therefore a major concern of forensic accountant to carry out the effective investigation as well as the performance of the individuals related with the criminal activities. This study examined the role of the forensic accountant in the prevention and detection of fraud in business organisations in Nigeria. The study used a survey design using questionnaire to obtain data from 328 accountant involved in audit firms (AF), Deposit Money Banks (DBM), and small and medium size enterprises (SMEs). Data were analyzed using SPSS 24 and results were considered significant at p < 0.05. Results revealed that majority of business organisations perform better in fraud control with a mean value of 3.52 ±1.25SD. Moreover, there was a significant relationship between internal control and forensic accounting (P= 0.021) though only operating efficiency is positively related to forensic accounting. The result of the model summary of the regression analysis for the operational efficiency model shows R-squared value of 0.406, indicating that about 40.6% of variations in operational efficiency is explained by forensic accounting. The ANOVA result of the model shows that F-statistic value of 126.522 with significance value of 0.000 which indicates that F-statistic is significance (p < 0.05). Forensic accounting was found to be statistically significant in affecting the information and communication technology of business organisations in Nigeria. Findings revealed that forensic accounting play an essential role in the detection and prevention of fraud in business organisations in Nigeria.
Keywords: Forensic Accounting; Fraud; Business Organisation; Information and Communication Technology